2009
DOI: 10.1097/aln.0b013e31819b602b
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p75 Neurotrophin Receptor Attenuates Isoflurane-mediated Neuronal Apoptosis in the Neonatal Central Nervous System

Abstract: Background Exposure to anesthetics during synaptogenesis results in apoptosis and subsequent cognitive dysfunction in adulthood. Probrain derived neurotrophic factor (proBDNF) is involved in synaptogenesis and can induce neuronal apoptosis via p75 neurotrophic receptors (p75NTR). proBDNF is cleaved into mature BDNF (mBDNF) by plasmin, a protease converted from plasminogen by tPA that is released with neuronal activity; mBDNF supports survival and stabilizes synapses through TrkB receptors. We hypothesized that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
220
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(230 citation statements)
references
References 55 publications
8
220
0
2
Order By: Relevance
“…It is important to note that the reasons for the disparity between the two states in this study are likely multifaceted and may result from differences in stress levels, auditory arousal, and the effect of anesthetics. Indeed, volatile anesthesia (such as isoflurane) decreases excitatory and increases inhibitory transmission (Gomez and Guatimosim, 2003;Ouyang and Hemmings, 2005), affects neuroplasticity, and can alter BDNF expression (Lu et al, 2006;Head et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the reasons for the disparity between the two states in this study are likely multifaceted and may result from differences in stress levels, auditory arousal, and the effect of anesthetics. Indeed, volatile anesthesia (such as isoflurane) decreases excitatory and increases inhibitory transmission (Gomez and Guatimosim, 2003;Ouyang and Hemmings, 2005), affects neuroplasticity, and can alter BDNF expression (Lu et al, 2006;Head et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…There are some data to support this mechanism. Active axons normally release tPA and proBDNF [21]. The tPA cleaves plasmin to plasminogen which in turn converts proBDNF to BDNF.…”
Section: Mechanism Of Anaesthesia-induced Apoptosismentioning
confidence: 99%
“…Activation of p75NTR receptor, also called the "death receptor," leads to actin depolymerization and apoptosis. Head et al [50] demonstrated that isolurane causes apoptosis in the neonatal mice brain through this pathway.…”
Section: Pathogenesismentioning
confidence: 99%